Exploring the relationship between dialogic teacher talk and students' persuasive writing. (February 2021) - Al-Adeimi, Shireen; O'Connor, Catherine
Abstract: Studies have documented the importance of dialogic classroom discourse for supporting academic outcomes such as reading comprehension and vocabulary development. This study examines the relationship between teacher talk during whole-classroom discussions in 42 classrooms and post-discussion persuasive essays from students in grades four through seven (n = 471). Teacher talk was coded by type of question (contestable, semi-open, or quiz-like) and teachers' follow-ups (prompting, pressing for reasoning, active listening), and further categorized as indicating either high or low levels of dialogic talk. Multilevel modeling that accounts for student participation rate, discussion topic, and students' demographic information shows that high dialogic teacher talk positively predicts students' persuasive essay scores, while low dialogic teacher talk negatively predicts their scores. The study supports existing hypotheses about the role of teacher dialogic talk in whole-class settings. Highlights: Specific teacher talk moves during discussions are linked to students' persuasive essay scores. High teacher dialogic talk positively predicts students' persuasive essays. Low teacher dialogic talk negatively predicts students' persuasive essays. Open-ended questions and teacher follow ups positively predict students' scores. Quiz-like and semi-open questions negatively predict students' scores.